Model development prevention and control of TB/ HIV/ Syphilis/ HCV in prisons under Good Health Good Heart of Health Region 4 - Sukhon, Daecha (Journal of Medical and Public Health Region 4, 2023)
This research is research and development. The objective is study problems, obstacles of operations, evaluate results and development, and propose prevention and control models in prison. The sample group 53 cases were a prison nurse, Project manager of Good Health Good Heart, and executives of the organization. Data collection: use Inspection record form, in-depth interview, presenting a screening operation model in period, which were verified by 3 experts. The research period is from October 2021 to September 2022. Research area is covers 18 prisons in Health region 4. Data analysis: quantitative with descriptive statistics presented as numbers and percentages, while qualitative with content interpretation and analysis. Research results. 10,992 New prisoners. All cases received CXR, lung abnormalities were found 686 cases (6.24%), Sputum collection for Gene Xpert examination TB was found 69 cases (0.63%). 22,840 old prisoners. lung abnormalities were found 2,510 case. Sputum collection for Gene Xpert examination TB was found 126 cases (0.56%). Health Region 4 screened TB all prisoners at 100%. Because there are 3 X-ray Digital Mobile. HIV/ Syphilis/ HCV screening New Prisoners were 68.33%, 50.43% and 34.52% respectively. Found an infected person 1.20%, 1.66%, 1.07% respectively. 3 prisons had 100% screening results. As a result of the commitment of project manager for Good Health Good Heart, screening Kits enough, executives of the organization supported. Policy recommendations 1) Implement operational models and develop communicable disease screening in prisons to achieve targets. 2) Push the cost of screening tests for HCV/ syphilis to be covered by the National Health Security Office. 3) "SET ZERO" policy for the prevention and control of TB/ HIV/ syphilis/ HCV in prisons.